Conceptual Ambiguities in Coretax: A Philosophical Examination of Legitimacy, Efficiency, and Justice in Digital Tax Administration - Chelsya Chelsya; Emillia Sastrasasmita; Abdul Hamid Habbe; Gagaring Pagalung (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to clarify conceptual ambiguities in the discourse on digital taxation by distinguishing between Coretax-T, as a digital tax administration system, and Coretax-N, as a normative concept of digital tax legitimacy. Research Method: The study employs a conceptual analysis approach using conceptual mapping, conceptual decomposition, internal consistency testing, and case application to tax policy documents, political philosophy literature, and studies on digital governance. Results and Discussion: The findings indicate that using the term “Coretax” in two senses leads to inconsistencies in arguments surrounding the evaluation of digital taxation. The Lockean tradition offers the most consistent analytical framework, whereas the Rawlsian and utilitarian approaches still face conflicts of principle and methodological issues. Implications: An evaluation of digital taxation should not be based solely on administrative efficiency, but must also take into account procedural legitimacy, distributive justice, and access to digital justice. Originality: The novelty of this research lies in the conceptual distinction between Coretax-T and Coretax-N as the foundation for a philosophical evaluation of digital taxation.